South Slavic Women’s Transgenerational Trauma Healing Through Oral Memory Practices: Women War Crimes and War Survivors - Anderson, Danica (Lexington Books, 2023)
South Slavic Women’s Transgenerational Trauma Healing through Oral Memory Practices: Women War Crimes and War Survivors explains that Kolo-Informed Trauma Treatment is a clinical, cultural, psychological, and neurobiological approach that draws upon the rich scientific UNESCO intangible cultural heritage and embodied practices of the South Slavic Kolo-circle movement format or somatic folk dance. The author argues that Slavic oral memory practices are not in fact worthless or outdated in healing trauma. The inclusion of the little-known or rarely researched women who have experienced war crimes and war trauma demonstrates the intrinsic depth and female indigenous resources aligning with many scientific interdisciplinary fields and women’s human rights. Central to the Kolo-Informed Trauma Treatment is the profound recognition of the importance of women’s cultural memory and somatic oral traditions to evolve towards communal healing. Women’s memory narrative enables the South Slavic people to have profound communal approaches to offer insights into the effects of war trauma, advocating paths towards thriving. Through a recalibration with the relationship of women as valued resources and prominence as creators of healing cultures, South Slavic women’s communal healing practices, if orchestrated on a planetary scale, elaborate inclusive dynamic homeostasis.